Effect of spatial processes and topography on structuring species assemblages in a Sri Lankan dipterocarp forest. Issue 2 (1st February 2014) - Punchi-Manage, Ruwan; Wiegand, Thorsten; Wiegand, Kerstin; Getzin, Stephan; Gunatilleke, C. V. Savitri; Gunatilleke, I. A. U. Nimal
Abstract : Niche and neutral theories emphasize different processes that contribute to the maintenance of species diversity and should leave different spatial structures in species assemblages. In this study we used variation partitioning in combination with distance‐based Moran's eigenvector maps and habitat variables to determine the relative importance of the effects of pure habitat, pure spatial, and spatially structured habitat processes on the spatial distribution of tree species composition and richness in a 25‐ha tropical rain forest of Sinharaja/Sri Lanka. We analyzed the contribution of those components at three spatial scales (10 m, 20 m, and 50 m) for all trees and the three life stages: recruits, juveniles, and adults. At the 10‐m scale, 80% of the variation in species composition remained unexplained for recruits and adults, but only 55% for juveniles. With increasingly broader scales these figures were strongly reduced, mainly by an increasing contribution of the spatially structured habitat component, which explained 4–30%, 20–47%, and 8–35% of variation in species composition for recruits, juveniles, and adults, respectively. The pure spatial component was most important at the 20‐m scale and reached 20%, 32%, and 23% for recruits, juveniles, and adults, respectively. The spatially structured habitat component described variability at broader scales than the pure spatial component. Our results suggest that stochastic processes and spatially structuring processes of community dynamics, such as dispersal limitation and habitat association, contributed jointly to explain species composition and richness at the Sinharaja forest, but their relative importance changed with scale and life stage. Species assembly at the local scale was more strongly impacted by stochasticity, whereas the signal of habitat was stronger at the 50‐m scale where plant‐scale stochasticity is averaged out. Recent research points to an emerging consensus on the relative contribution of stochasticity, habitat, and spatial processes in governing community assembly, but how these components change with life stage, and how this is influenced by sample size, remains to be explored.